Single Ascending Dose Safety and Pharmacokinetics of CDRI-97/78: First-in-Human Study of a Novel Antimalarial Drug. (27th March 2014) - Shafiq, N.; Rajagopalan, S.; Kushwaha, H. N.; Mittal, N.; Chandurkar, N.; Bhalla, A.; Kaur, S.; Pandhi, P.; Puri, G. D.; Achuthan, S.; Pareek, A.; Singh, S. K.; et al.
Abstract : Background . CDRI 97/78 has shown efficacy in animal models of falciparum malaria. The present study is the first in-human phase I trial in healthy volunteers. Methods . The study was conducted in 50 healthy volunteers in a single, ascending dose, randomized, placebo-controlled, double blind design. The dose ranges evaluated were from 80 mg to 700 mg. Volunteers were assessed for clinical, biochemical, haematological, radiographic, and electrocardiographic parameters for any adverse events in an in-house facility. After evaluation of safety study results, another cohort of 16 participants were administered a single oral dose of 200 mg of the drug and a detailed pharmacokinetic analysis was undertaken. Results . The compound was found to be well tolerated. MTD was not reached. The few adverse events noted were of grade 2 severity, not requiring intervention and not showing any dose response relationship. The laboratory and electrocardiographic parameters showed statistically significant differences, but all were within the predefined normal range. These parameters were not associated with symptoms/signs and hence regarded as clinically irrelevant. Mean values of T 1 / 2, MRT, and A U C 0 - ∞ of the active metabolite 97/63 were 11.85 ± 1.94 h, 13.77 ± 2.05 h, and 878.74 ± 133.15 ng·h/mL, respectively Conclusion . The novel 1, 2, 4 trioxane CDRI 97/78 is safe and will be an asset in malarial therapy if results are replicated in multiple dose studies and benefit is shown in confirmatory trials.